Problematika Pendidikan di Mesir dalam Cerpen Fî Al-Qithâr Karya Mahmoud Taymour (Analisis Sosiologi Sastra) - Mohammad Dzulkifli (Alfaz (Arabic Literatures for Academic Zealots), 2019)
This study aims to reveal the educational problems of Egyptian society contained in the "Fi al-Qithar" short story by Mahmoud Taymur and its relevance to the social reality of Egyptian society in the early 19th century. The reason the researchers chose the "Fi al-Qithar" short story was because it was the first Modern Arabic short story that appeared in Egypt that represented a lot of the social reality of society and the pattern of life in Egypt at that time. This research includes qualitative research by using Sociology of Literary theory, and uses hermeneutic analysis methods to interpret and explain to the reader about the meaning contained in the short story. The results of this study conclude that there are social phenomena adopted by the authors in this short story, including the problem of educational equity, social inequality, urban elite slavery and government officials over ordinary people such as farmers and laborers, and the role of religious leaders in dealing with problems happens in the midst of society.